Parents’ Interest toward Parenting Education Program in the Covid-19 Pandemic: a Study on Elementary Schools - Slamet Santoso; Rima Febrianti; Shodiq Hutomono; Muchhamad Sholeh; Fatona Suraya (International Conference on Science, Education, and Technology, 2021)
The ability of parents in educating and caring for children, of course, varies due to differences in social, cultural, and educational backgrounds. This is the main problem in the education process at the elementary school level during the pandemic, which requires parents to be able to become teachers for their children. This study creates a program to educate parents to improve their insight and knowledge to be good teachers when learning at home. This research investigates parents' interest in the given program through a mixed-methods design using a set of questionnaires and interview rubric as the main instrument. Data analysis using sequential explanatory strategy. The results showed that classically 84.32% of parents' interest in educational programs through parenting classes at the elementary school level was included in the very good category. The quantitative data above is reinforced by interviews with 14 parents and teachers who stated that all parents and teachers strongly agreed with the program because it could build parents' awareness of the importance of education for children and increase their knowledge and abilities. So it can be concluded that the parenting class program can educate parents and increase their insight, knowledge, and abilities, so that they can become good teachers when learning at home.